Psychometric Properties of a Spanish Version of the Basic Needs Satisfaction in Sports Scale - Pineda-Espejel, H. Antonio; López Gaspar, Icela; Guimaraes, Andrea Carmen; Martínez Zavala, Sonia; Morquecho-Sánchez, Raquel; Morales-Sánchez, Verónica; Dantas, Estelio Henrique (Frontiers in Psychology, 2019)
The Basic Needs Satisfaction in Sport Scale (BNSSS) is an instrument designed to measure the level of satisfaction of the three basic psychological needs in sports, according to The Self-Determination Theory. The purpose of this research was to adapt BNSSS to Mexican Spanish and analyze its psychometric properties (factorial validity, factorial invariance, internal consistency, convergent validity, nomological, and criterion validity). Thus, 542 athletes (average age: 12.06 years; SD = 1.83) were asked to answer a set of questionnaires. Confirmatory factor analyses supported both the structure of five related factors and the trifactorial structure after eliminating an item. Nevertheless, the reliability analysis indicated strong internal consistency, and the average variance extracted from the subscales was acceptable except for the volition factor, thus supporting the trifactorial model. Scores derived from the instrument’s three factors offered evidence of the criterion validity, through a positive and meaningful relation with enjoyment and subjective vitality. Moreover, results of multi-sample analysis supported that factorial structure is invariant between men and women. In conclusion, this BNSSS Spanish version displayed adequate psychometric properties, showing that it can be used to measure the three basic psychological needs.